(untitled) (Research, Society and Development, 2021)
To determine the resistance profile of bacteria isolated from surfaces and utensils of the food and nutrition unit of a public hospital in the city of Recife-PE. Surface samples were collected, transferred to the Brain Heart Infusion (BHI) broth, and incubated for 24 h at 35 °C. After the identification of Staphylococcus aureus, Enterococcus spp. and enterobacteria, resistance profiles were determined according to the Clinical and Laboratory Standards Institute. Among the 10 samples collected, 6 presented Gram-positive bacteria and all showed enterobacteria. Methicillin-resistant Staphylococcus aureus (MRSA) was present at the snack and dessert preparation counter and the cold cuts counter. The sites with the highest number of resistant microorganisms were the dishwashing sink with the species Klebsiella pneumoniae (ESBL and MBL), Salmonella spp. (KPC) and Providencia spp.; snack and dessert table with Klebsiella pneumoniae (ESBL) and Salmonella spp. (ESBL and KPC); and dining counter with Providencia spp. and Citrobacter spp. (MBL). Surfaces, equipment, and hands of food handlers are sources of contamination by bacteria with resistance profiles, making it necessary the implementation and supervision of good practices of cleaning surfaces, equipment and hands of handlers, as well as educational measures in the hospital’s food and nutrition unit.